Habilidades comunicativas y su incidencia en el proceso del desarrollo cognitivo en estudiantes del segundo año de básica paralelo “a” de la Escuela de Educación Básica “San José” Parroquia Clemente Baquerizo cantón Babahoyo Provincia de Los Ríos - Mora Ortiz, Adriana Cecilia (2019)
Communication skills play a very important role in the teaching-learning process. It is complex to develop intellectual or professional skills if there are problems with the development of communication skills. It is important to develop communication skills to be able to effectively what we think, feel and want. The need to interact with other human beings and what we constantly do in all the movements of our life. Without communication, we are not at the level of development in which we are. Good or bad communication can develop positive or negative effects on our relationships. So you will agree with us that communication constitutes a fundamental pillar in our social life and is a powerful instrument of change. This work is of social interest, since unfortunately there are still many teachers who do not stimulate cognitive development in their students, having a huge impact on the teaching and learning process. This work directly benefited the educational community, and the development of the children of this institution